2001
DOI: 10.1081/ncn-100001437
|View full text |Cite
|
Sign up to set email alerts
|

EFFICIENT METHODS FOR THE SYNTHESIS OF [2-15N]GUANOSINE AND 2′-DEOXY[2-15N]GUANOSINE DERIVATIVES

Abstract: The nucleophilic addition-elimination reaction of 2',3',5'-tri-O-acetyl-2-fluoro-O6-[2-(4-nitrophenyl)ethyl]inosine (8) with [15N]benzylamine in the presence of triethylamine afforded the N2-benzyl[2-15N]guanosine derivative (13) in a high yield, which was further converted into the N2-benzoyl[2-15N] guanosine derivative by treatment with ruthenium trichloride and tetrabutylammonium periodate. A similar sequence of reactions of 2',3',5'-tri-O-acetyl-2-fluoro-06-[2-(methylthio)ethyl]inosine (9) and the 6-chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Therefore, improved methods have been reported for C-6 chlorination of 2′-deoxyguanosine 3′,5′-diacetate with careful control of reaction conditions 5,6. In addition to C-6 chlorination of the guanine nucleosides, facile synthesis of the O 6-arylsulfonates is also known 612.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, improved methods have been reported for C-6 chlorination of 2′-deoxyguanosine 3′,5′-diacetate with careful control of reaction conditions 5,6. In addition to C-6 chlorination of the guanine nucleosides, facile synthesis of the O 6-arylsulfonates is also known 612.…”
Section: Introductionmentioning
confidence: 99%
“…We found that at elevated temperature (100 °C), the reaction took place very quickly as indicated by the instant disappearance of cloudy 2 in 1,4-dioxane with the addition of DIAD. [11] Under such conditions, both silyl protecting groups were stable. The reductive amination reaction between the exocyclic amine in 3 with paraformaldehyde and sodium cyanoborohydride (NaBH 3 CN) in acetic acid at 40 °C resulted in sequential methylation of exocyclic amine to give a mixture of N 2 -methyl and N 2 , N 2 -dimethyl guanosine derivatives 4a and 4b .…”
mentioning
confidence: 99%
“…[9] Protection of O 6 using pnitrophenylethyl group by the treatment of 2 with p-nitrophenylethanol in the presence of triphenylphosphine (Ph 3 P) and diisopropyl azodicarboxylate (DIAD) gave 3 in 92 % yield. [11] Ther eductive amination reaction between the exocyclica mine in 3 with paraformaldehyde and sodium cyanoborohydride (NaBH 3 CN) in acetic acid at 40 8 8Cresulted in sequential methylation of exocyclic amine to give amixture of 4aand 4b.Depending on the amount of paraformaldehyde and NaBH 3 CN used, either 4a or 4b could be obtained as major products.A ll the protecting groups in intermediate 3 remained stable under the acidic conditions.T reatment of 4a/ 4b with hydrogen fluoride pyridine removed the 3',5'-di-tertbutylsilyl group quantitatively while keeping 2'-TBDMS intact to give intermediates 5a/5b.5 '-Tritylation gave the mixture of 6a/6b.A lthough two types of methylated derivatives could be readily separated by column chromatography at 4a/4b or 5a/5b stage,itismore efficient to separate 6a and 6b by column chromatography.S ubsequent 3'-phosphitylation 6a and 6b under standard conditions provided m 2 2 G phosphoramidite 7a and m 2 Gp hosphoramidite 7b in 88 % and 85 %yield, respectively.…”
mentioning
confidence: 99%
“…We started our synthesis from guanosine 1 by selective protecting 3′,5′‐hydroxyls with di‐ tert ‐butylsilyl group and 2′‐hydroxy with TBDMS in a “one‐pot” reaction to give intermediate 2 in 75 % yield . Protection of O 6 using p ‐nitrophenylethyl group by the treatment of 2 with p ‐nitrophenylethanol in the presence of triphenylphosphine (Ph 3 P) and diisopropyl azodicarboxylate (DIAD) gave 3 in 92 % yield . The reductive amination reaction between the exocyclic amine in 3 with paraformaldehyde and sodium cyanoborohydride (NaBH 3 CN) in acetic acid at 40 °C resulted in sequential methylation of exocyclic amine to give a mixture of 4 a and 4 b .…”
Section: Figurementioning
confidence: 99%